Nitretação a plasma de aço inoxidável austenítico sinterizado com fluxo pulsado de nitrogênio - Pereira, Diandra Grossmann (2019)
Although stainless steels are widely used in industry, the need for surface treatments such as plasma nitriding is common. However, recent studies show the formation of cracks when this treatment is performed on AISI 316L sintered austenitic stainless steel. This is an undesired phenomenon, since it can promote the access of corrosive media to the interior of the material and accelerate the corrosion process, and a possible explanation for this occurrence is the level of residual stress resulting from the formation of expanded austenite. Based on this, this paper aims to study the effect of nitrogen pulses as a way to control the nitrogen potential and prevent the formation of cracks in AISI 316L sintered stainless steel. Nitrites of 4 hours and 8 hours with continuous nitrogen fluxes, samples that showed cracks in the layer, as well as nitriding with pulsed nitrogen flow were performed, and the results showed a reduction of the cracks in the samples of 8 hours with pulsed flow in relation to the samples of 8 hours with continuous flow, and an elimination of the cracks in the samples of 4 hours, showing that this can be an important tool of control of tensions and cracks in sintered stainless steels.